Folk didacticism as reflected in the thematic pattern of the composo. - Perez, Elnora R (1988.)
This study entitled "Folk Didacticism as Reflected in the Thematic pattern of the Composo" is based on the thirteen samples gathered from six manugcomposos of Constancia, Jordan, Guimaras., Findings reveal that the composo has four basic elements unlike the Mexican corrido which has six. In its social context, folk didacticism is on modes of conduct. The approved behaviors are heroism , industry and helpfulness. Disapproved behaviors are loitering, sibling, rivalry, dishonesty in livelihood and suicide. Other non-behavioral subjects are attitudes on people and public dance. Folk didacticism is preventive in nature. It facilitates the maintenance of peace and order of Constancia. Sometimes not all of what the composo preaches are observed. Due to necessities, people are compelled to display unfavorable behavior.
Thesis (Undergraduate, Bachelor of Arts in Comparative Literature) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo.
Keywords: Composo